Menciptakan Citra Merek yang Kuat dengan Desain Logo UMKM Graha Pangsit - Vega, Amarlia; Arif, Sonhaji; Satrio, Putra Uji Deva; Andari, Trias Widha; Utami, Athika Dwi Wiji; Hartiningrum, Amalia (Jurnal Bisnis Indonesia, 2024)
Graha Pangsit has succeeded in distinguishing itself with its unique taste. However, it still does nothave a good brand image in society. So it is important to recognize that building a strong brand imagerequires more than just an extraordinary product. It also involves creating a logo that can represent aunique identity. Qualitative Research Methods include analysis of literature studies, interviews andinvolving related parties directly in the PKM process to gain an in-depth understanding of thebranding strategy used by UMKM Graha Pangsit. Graha Pangsit logo design The depiction of a bowlof wonton noodles presented in the visual as well as the red flag that forms the badge means that thisnoodle dumpling is a champion in taste. The choice of red also means leader. Effective logo designcan be the key to creating a strong brand image. A logo development process that takes into accountthe unique character of the brand, a deep understanding of the market, and collaboration betweenMSME owners and designers can produce significant results in improving brand image and businessgrowth. In the context of Graha Pangsit MSMEs, the logo design has helped them attract the attentionof new customers and strengthen relationships with their loyal customers, allowing them to competein an increasingly busy culinary market.Keywords: Brand Image; Logo; MSMEs